A manifestação da memória nas obras Os Ratos e O Louco de Cati - Rossato, Bianca Deon (2009)
This work investigates the manifestation of memory in the life trajectory of the protagonists from the novels Os ratos (1935) and O louco do Cati (1942), by the writer Dyonelio Machado. For that purpose, the most relevant expressions of the memory mechanism of each main character are analyzed, so that it is possible to identify their peculiarities; the reasons that impel the appearance of such recollections and not others, in the characters everyday living; and the way through which those remembrances interfere in their attitudes. The research that is a bibliographical one used as bases the theories by Henri Bergson, in Matter and Memory (1896), and by Sigmund Freud, in Project for a scientific psychology (1895) and Screen memories (1899). By the end of the search, it was noticed that certain memories redirect the actions of the protagonists in such a way that prevents them from making some decisions. It was also observed that, although the protagonists frequently have notion about the importance of certain postures, they do not feel capable of such behavior because their recollections reinforce the lack of attitudes. Besides, it was verified the existence of painful remembrances that are concealed by other ones, because of their harmful content, usually related to the person s childhood, that avoid the outcoming of displeasure in the individual s psyche